RECRUITMENT OF NEW EMPLOYEE USING SELECTION PROCESS FOR DETERMINING DECISIONS WITH THE PREFERENCE SELECTION INDEX METHOD - Pandu Adi Cakranegara; Efendi; Aditya Wardhana; Tienni Mariana Simanjorang; Revi Sesario (Sean Institute, 2022)
The most important thing for companies is to hire new people who have the skills and qualities needed for the job or acceptance offered. The ability of a company to run well depends a lot on the quality of its employees. The issue of hiring people and getting the finest applicants can be overcome with the aid of decision-making procedures. In a recruitment process, there are many selection mechanisms in businesses with varying criteria. In this study, decision-makers are selecting candidates for employment based on specified criteria, including an intelligence test (C1), an interview test (C2), a test of skills and abilities (C3), an assessment of attitudes and behaviors (C4), and work experience (C5). The calculating approach employs the Preference Selection Index (PSI) method because it can be applied to situations with multiple criteria and attributes and does not require the decision maker to calculate the weights of the criterion. The 3 best option candidates for the employees with the greatest PSI value, which is PSI = 0.88186, are determined by the results of the final PSI method computation from 5 alternatives.